Enhanced hydrogen production over Ni-M alloys (M = Co, Zn) formed from hydrotalcite-derived structures for aqueous-phase reforming of xylose - Owen Khosashi; Yoondo Kim; Seoyeon Cho; Hyangsoo Jeong; Youngmin Kim; Sung Pil Yoon; Kwang Ho Song; Suk Woo Nam; Choi, Sun Hee; Hyuntae Sohn (Elsevier BV, 2025)
Non-noble metal-based catalysts derived from Ni-hydrotalcite, incorporating various metal promoters (Cu, Co, Ca, Mg, and Zn) were studied for Aqueous-phase reforming (APR) of xylose. The formation of a hydrotalcite structure in the as-prepared samples and their transition into mixed-metal oxides upon calcination was confirmed. During subsequent reduction, more reducible promoters (Cu, Co, and Zn) formed alloys with Ni, while less reducible promoters (Ca and Mg) remained in their oxide form within the catalyst. NiZnAl and NiCoAl catalysts outperformed NiAl, achieving higher hydrogen yields and production rates per gram of Ni for APR of xylose. NiZnAl exhibited the highest catalytic activity, owing to the formation of a NiZn alloy with increased electron density, leading to a lower surface acidity and enhanced adsorbate？metal interactions, thereby improving the reforming activity. The proposed Ni-hydrotalcite-derived catalyst offers a simple and cost-effective solution for scalable xylose reforming with high catalytic performance and stability.